Almost a century and a half of traditional reception: Universality or internationality of Ricardo Palma - Vega Cernuda, Miguel Ángel (2019)
This paper examines the universality and internationality categories of Ricardo Palma's work. It is an analysis of the phenomenon in the reception of the Traditions. Ideas and procedures from the emerging Bibliometrics of the scientific literature have been applied to show the considerable gap between the presence of Palma's works in the Hispanic letters (editorialist, criticism, etc.) compared to the universal ones (editions in other languages).